2021
DOI: 10.3389/fimmu.2021.730404
|View full text |Cite
|
Sign up to set email alerts
|

Silent SARS-CoV-2 Infections, Waning Immunity, Serology Testing, and COVID-19 Vaccination: A Perspective

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus causes a spectrum of clinical manifestations, ranging from asymptomatic to mild, moderate, or severe illness with multi-organ failure and death. Using a new machine learning algorithm developed by us, we have reported a significantly higher number of predicted COVID-19 cases than the documented counts across the world. The sole reliance on confirmed symptomatic cases overlooking the symptomless COVID-19 infections and the dynamics of waning imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…While 0 (0%) and 54 (6%) control subjects (HC & NT) had IgG Sp levels less than 50 AU/mL in the 2D and 3D Co-mV format experiments ( Figure S2 and Table 2A ). In particular, previous reports have shown that IgG Sp antibody titers of ≥ 4160 AU/mL correspond to a neutralizing titer ( 40 , 41 ) and here, we have found that 1 in 6 IC patients (16%) was able to generate neutralizing titers after 2 Co-mV doses compared to healthy controls (64%) ( Table 2B ). Although, the 3 rd dose improved the IgG response over neutralizing titer of 4160 AU/mL, despite 3 Co-mV doses, still over half the population (57%) in the immunocompromised SOT group had IgG response below the neutralizing titers ( Table 2B ).…”
Section: Resultssupporting
confidence: 75%
“…While 0 (0%) and 54 (6%) control subjects (HC & NT) had IgG Sp levels less than 50 AU/mL in the 2D and 3D Co-mV format experiments ( Figure S2 and Table 2A ). In particular, previous reports have shown that IgG Sp antibody titers of ≥ 4160 AU/mL correspond to a neutralizing titer ( 40 , 41 ) and here, we have found that 1 in 6 IC patients (16%) was able to generate neutralizing titers after 2 Co-mV doses compared to healthy controls (64%) ( Table 2B ). Although, the 3 rd dose improved the IgG response over neutralizing titer of 4160 AU/mL, despite 3 Co-mV doses, still over half the population (57%) in the immunocompromised SOT group had IgG response below the neutralizing titers ( Table 2B ).…”
Section: Resultssupporting
confidence: 75%
“…Although blood transfusion is an important part of the health care system, the adequate and safe availability of blood products to meet patients’ needs became a major concern during the COVID-19 pandemic [ 29 ]. Generally, it is believed that it is a key time to focus on asymptomatic (with no symptoms) and oligosymptomatic (with so mild symptoms that remain unrecognized) COVID-19 patients as they can be silent reservoirs to circulate SARS-CoV-2 infections [ 30 ].…”
Section: Discussionmentioning
confidence: 99%